STUDI KELAYAKAN ASPEK TEKNIS DAN TEKNOLOGI UMKM RAKIK PISANG RAHMAT DI KABUPATEN AGAM - Marzhanda, Yola; Annisa, Nola Nurma; Intan, Intan; Auliya, Yuka Amarasri; Yahya, Lucky Mahesa (KOLEGIAL, 2024)
In advancing the productivity and efficiency of a business, a business feasibility study is needed to assess and analyze various aspects in the development of business operations. For this reason, this study aims to review the feasibility of business studies on the UMKM Rakik Pisang Rahmat in Agam Regency, which is engaged in the food industry. This type of research is descriptive research. Data collection techniques used in obtaining data are observation and interviews. The analytical method used is the analysis of technical and technological aspects. The results of the study show that the Rakik Pisang Rahmat business is in a strategic area which allows the business to increase effectiveness by managing the availability of raw materials and production capacity, but still uses traditional technology in its production activities, so that the Rakik Pisang Rahmat business is not feasible from a technical and technological perspective.